KEPATUHAN MENJALANKAN DIET PENDERITA DM DI PUSKESMAS PB SELAYANG II MEDAN - Butar-Butar, Maria Haryanti; Lasmawanti, Sri; Afina, Afina; Maryanti, Endang (CV. Kalimasada Group, 2023)
Indonesia is estimated to reach 16.7 billion by 2045. The purpose of the activity is to make a dedication to the community with a health promotion activity to the public with the title compliance running diabetes mellitus diet in patients with diabetes in Puskesmas PB. The method of dedication to the community is conducted by teaching health education in the form of lectures using tools such as lifts and brochures that are distributed to the society and also as a tool for care and for patients with diabetes and taking diabetes medication as well as family members who have effects from the descent of people with diabetes. The post-test score with an average of 92.68% of participants responded correctly is greater compared to the pre-test rating of 77.49%. Public knowledge in Puskesmas PB. The field has grown between 80-90% after being given approval of dietary compliance with diabetes, the food and nutritional requirements of the diabetic and healthy living for his offspring. It is necessary to carry out advanced activities related to the training of adherence to the diet consumed by the sufferers and how to manage good and correct food for patients or people with diabetes mellitus and their offspring to maintain a diet with a healthy lifestyle and can be information for other communities